Multisession Radiosurgery for Sellar and Parasellar Benign Meningiomas: Long-term Tumor Growth Control and Visual Outcome. Issue 5 (May 2016) - Marchetti, Marcello; Bianchi, Stefania; Pinzi, Valentina; Tramacere, Irene; Fumagalli, Maria Luisa; Milanesi, Ida Maddalena; Ferroli, Paolo; Franzini, Angelo; Saini, Marco; DiMeco, Francesco; Fariselli, Laura
Abstract : BACKGROUND: Concern about radiation-induced optic neuropathy (RION) has governed recent thinking about the role of radiation therapy in the treatment of meningiomas involving the anterior optic pathways. Despite this concern, during the last few years, the use of radiosurgery for such lesions has increased steadily. OBJECTIVE: To define both the tumor control rate and the risk of RION over a long-term follow-up period in a large cohort of patients treated with multisession radiosurgery. METHODS: The local control and visual outcome of 143 patients who underwent multisession radiosurgery (mRS) were evaluated. Neurological outcome was also analyzed. The data for the present study were obtained from a prospectively maintained database. RESULTS: The mean follow-up was 44 months (range, 12-113 months). All patients underwent mRS. The median prescription dose was 25 Gy delivered in 3 to 5 fractions. The prescription isodose, which typically encompassed at least 95% of the tumor, ranged from 65% to 86% (median, 80%). The mean tumor volume was 11.0 cm 3 (range, 0.1-126.3 cm 3 ; median, 8 cm 3 ). The progression-free survival at 3, 5, and 8 years was 100%, 93%, and 90%, respectively. Compared with baseline, visual function improved in 36% of patients, whereas 7.4% experienced a worsening in visual function (5.1% excluding the patients with progressive disease). CONCLUSION: Good local control rate and a low risk of RION indicate that mRS is a safe and effective treatment option in cases of large meningiomas. ABBREVIATIONS: AOP, anterior optic pathway AVP, anterior visual pathway mRS, multisession radiosurgery PD, progressive disease RION, radiation-induced optic neuropathy sRS, stereotactic radiosurgery